The Effect of Car, BOPO, NPF, and FDR on Profitability of Sharia Commercial Banks in Indonesia - Saleh Sitompul; Siti Khadijah Nasution (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Operational Costs on Operating Income (BOPO), Non Performing Financing (NPF) and Financing to Deposit Ratio (FDR) to Profitability with Return on Assets (ROA) in Indonesian Commercial Banks . The population in this study were 13 Sharia Commercial Banks in Indonesia registered in the Financial Services Authority and Bank Indonesia from 2013-2017, with a total sample of 6 Islamic Commercial Banks. The analytical method used is descriptive statistics, classic assumption tests, and multiple linear regression for hypothesis testing. The results showed partially that the Operational Cost of Operational Income had a significant negative effect on Return on Assets, while the Capital Adequacy Ratio, Non Performing Financing and Financing to Deposit Ratio did not affect Return on Assets of Islamic Commercial Banks in Indonesia. Simultaneously, the Capital Adequacy Ratio, Operational Cost to Operaional Revenue, Non Performing Financing and Financing to Deposit Ratio have a significant effect on Return on Assets of Islamic Commercial Banks in Indonesia. The predictive ability of the four variables on Return on Assets is 82%, while the remaining 18% is influenced by other factors outside of this research model.